Postpartum modern family planning among women living with HIV attending care at health facilities in Busia County, Kenya - Florence Zawedde Tebagalika; Derrick Kimuli; Dennis Walusimbi; Edna Nyang'echi; Louisa Ndunyu (BMC, 2024)
Abstract Background For women living with the human immunodeficiency virus (WLHIV), preventing untimed pregnancies during the postpartum period reduces vertical transmission and improves other maternal and child health outcomes. In Kenya, Busia County's HIV prevalence and mother-to-child transmission rate are higher than the national average yet uptake of postpartum family planning (PPFP) is generally low. This study examined health system factors influencing the consistent use of PP modern FP methods among WLHIV in Busia County. Methods A retrospective study involving 314 WLHIV with children aged 12-24 months who were chosen using systematic random sampling was conducted from February to March 2024 from outpatient clinics in Busia County. Additionally, 14 health providers were purposively sampled as key informants. Quantitative data was collected using a pretested questionnaire, while qualitative data was gathered through key informant interview guides. Quantitative data was analyzed using STATA 15 with descriptive statistics, logistic regression, and Chi-square tests, while a deductive thematic analysis was used for qualitative data. Results The mean age of the participants was 32.06 (± 6.00) with the majority (51.27) aged between 25 and 34 years, married (74.84%) and unemployed (77.39%). Overall, 73.25% had used postpartum (PP) modern family planning (FP) methods, but only 52.55% reported consistent use throughout the first year postpartum. The only factors found to increase the odds of PPFP use were being married (aOR 3.34, 95% CI 1.58-7.07, p = 0.002), being escorted by a preferred person during seeking maternal and child health services (aOR 2.29, 95% CI 1.36-3.83, p = 0.002), and perceiving that they were provided information on all types of FP (aOR 2.33, 95% CI 1.19-4.16, p = 0.012). Persistent stock-outs and inadequate counseling hindered consistent PPFP use. Conclusion The study identified gaps in the consistent use of PP modern FP methods among WLHIV in Busia County, influenced by the availability of FP information and health system factors. Addressing stock-outs and improving counseling during clinic visits and pregnancy are crucial for improving FP service delivery and reducing maternal and child health risks in high HIV-incidence areas like Busia County.